FORMULATION AND EVALUATION OF HERBAL-BASED ANTIDIABETIC TABLETS (International Journal of Food and Nutritional Sciences, 2021)
One of the most prevalent chronic illnesses in the world is diabetes mellitus, which arises due to the inability of the body to control the sugar in blood levels. Side effects of modern synthetic medicines to treat diabetes include weight gain, hypoglycemia and gastric ailments. Subsequently, personnel are contending with herbal formulations, which are less damaging, cheaper and readily available. The objective of this study was to prepare and test herbal-based antidiabetic tablets with plant extracts that are used in reducing the level of blood sugar. Tablet formulations were performed with standard procedures and assessments, such as tablet hardness, friability, disintegration and in-vitro release studies were performed. The findings showed that the tablets were satisfactory in their physical and chemical characteristics and showed potential value of hypoglycemic activity. The study argues the application of the herbal preparations as a complementary treatment or alternative therapy in treatment of diabetes.